The individual and combined associations of health behaviours with health-related quality of life amongst junior high school students in China - Liu, Ze Hua; Wang, Yi Lin; Yu, Yue Shuang; Ren, Yan; Zhang, Tong; Liu, Hong Qing; Wu, Xiu Yun (Frontiers in Public Health, 2023)
Objectives This study aimed to investigate the individual and joint associations of sedentary behaviour, physical activity (PA), sleep and breakfast eating on health-related quality of life (HRQoL) amongst Chinese junior high school students. Methods Data were from 783 junior high school students who participated in a health behaviour and health survey in Jining city of Shandong province of China. HRQoL was measured by the EuroQol five-dimensional questionnaire, youth version (EQ-5D-Y). Multivariable logistic and linear regressions were applied to examine the associations between health behaviours and HRQoL. Results Multivariable regression analyses showed that using a computer ≥ 2 h a day (vs. < 2 h/day) is associated with increased likelihood of having health problems in the three EQ-D-Y dimensions, including walking, looking after self and doing usual activities. Lower PA is associated with more problems in feeling worried, sad or unhappy, and with a lower visual analogue scale (VAS) score. Students who had insufficient sleep time (e.g., <7 h/day), and skipped eating breakfast were more likely to experience lower HRQoL in the dimensions of having pain or discomfort, and feeling worried, sad or unhappy, and a lower VAS score than those students who had longer sleep time and no breakfast skipping. Students who reported having the combined ≥ 2 unhealthy behaviours relative to the peers with 0–1 unhealthy behaviours were more likely to have lower HRQoL. Conclusion The findings in the present study underline the importance of promoting healthy behaviours in order to improve HRQoL amongst Chinese junior high school students.